Association of Iron Deficiency Anemia with Preterm Labor (Medical Forum Monthly, 2024)
Objective: To investigate the association of iron deficiency anemia as a cause of preterm labour.Study Design: Descriptive/cross sectional studyPlace and Duration of Study: This study was conducted at the Department of Obstetrics and Gynaecology, Nishter Hospital Multan from July 2016 to December 2016Materials and Methods: After approval from ethical committee of hospital, informed consent was taken from patients and data was entered and analyzed with computer software SPSS version 20. All numerical data was presented as mean and Standard Deviation and categorical data was presented as frequency and percentages. P Value of 0.05 was considered as significant.Results: Total patients included in this study were 196 (100%), all were females, in which 138 (70.4%) were house wives and 58 (29.6%) were working ladies. Mean Hb of the patients was 8.06 ± 1.42, mean of serum Ferritin was 12.90 ± 2.62, mean of delivery time was 34.78 ± 2.35, mean of BMI was 29.85 ± 1.67, mean of parity was 3.24 ± 1.37, mean of gravidity was 3.15 ± 1.23. Out of 196 (100%) it was observed that 128 (65.3%) were facing the condition of pre-term labor and 68 (37.7%) delivered normaly.Conclusion: Anaemia in pregnancy was found to be associated with increased risk for preterm labour.